Sectorial and qualitative differentiation for heterogeneous financial intermediaries - Guerrero López, Francisco Jesús (2022)
I study a variant of a Salop Circle, in which I analyze competition in banking systems. For this model, banks can differ in two ways, first in the quality of the financial service offered that could enhance the perceived benefits by the borrowers, and sectorally which could represent the knowledge that the banks have in a specific sector. Here, I analyze the interaction of heterogeneous lenders in the system, one bank that has the capacity of lending to each sector against business’s specialized banks. The analysis finds the possibility of multiple sets of market equilibrium and social optima. I restrict the analysis to the set that allows me to analyze the market failures when all possible combinations of banks are allowed.